Explaining human actions and environmental changes [ - Vayda, Andrew Peter (Lanham, Maryland : AltaMira Press, 2009)
In this selection of essays from decades of research, Vayda focuses on causal explanations of human and environmental interactions.
Description based on print version record
Includes bibliographical references (p 239-289) and index
Keywords: Ethnology; Human beings -- Effect of environment on; Human ecology